Infection prevention knowledge and practices among healthcare workers at a health facility in Makurdi, Benue State, Nigeria - Owoicho O. Amali; Renay H. van Wyk (AOSIS, 2023)
The ongoing COVId-19 pandemic has highlighted the critical importance of Infection prevention practices among healthcare workers. Prioritizing this crucial aspect of healthcare can mitigate the spread of infectious diseases and ensure the well-being of our healthcare heroes and their communities. The purpose of the research was to investigate the knowledge and practice of Infection prevention and control. The study was a cross-sectional study that used self-administered paper-based questionnaires. The study sample of 316 eligible healthcare workers were selected using stratified sampling. data was entered into EPI Info version 7.2 and exported to SPSS version 27 for analysis. The ethics committees of the University and the Hospital approved the study. The majority of participants 116 (36.7%) were nurses. The mean age was 34.79 years ± 8.37, 118 (37.30%) were male while 198 (62.7%) were female. Only 169 (53.9%) knew the recommended duration for hand washing. 132 (41.8%) of healthcare workers believed needles should be recapped following use. Healthcare workers were twice as likely to wash their hands before contact and five times more likely to wash their hands after contact with a patient, their bedding, or after a procedure (AOR 1.82, 95%CI 1.04-3.20), (AOR 4.51, 95%CI 1.76-11.54) respectively. Personal protective equipment (PPEs) were twice as likely to be unavailable (AOR 2.39, 95%CI 1.31‑4.37). The findings revealed suboptimal knowledge and practice of hand hygiene indicating the need for healthcare workers to be trained on IPC. PPE(s) must be provided for healthcare workers to improve compliance with IPC practices.